Formulation and quality control of Prunus domestica syrup, prepared according to Iranian Traditional Medicine - M. Hamzeloo-Moghadam; N. Danaifar; S.A. Mostafavi; H. Hajimehdipoor (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Prunus domestica (plum) has been considered as a useful remedy for several disorders in Iranian Traditional Medicine (ITM). It has cold and wet temperament and is used as syrup for hot temperament diseases such as hot headache and stomach disorders. In the present study, plum syrup has been formulated according to ITM manuscripts and quality control evaluations have been accomplished to present a suitable formulation. Methods: The fruits of Prunus domestica L. were macerated in water, then decocted. The mixture was filtered. The filtrate was concentrated to have a suitable viscosity. The extract was sweetened by adding sugar (1:2) and heated till sugar was completely dissolved. The final product was evaluated physicochemically and microbiologically according to standard protocols and total phenolics content of the syrup stability was determined. The syrup was assessed in accelerated condition (40 ºC) during 6 months. Results: The prepared formulation was a viscose and brown syrup with plum flavor and fragrance. No precipitation and cap locking were observed in the syrup. Dry residue, pH, density, viscosity and total phenolics of the syrup were found 43.1%, 3.49, 1.27 g/ml, 6.5 cP and 152.3 mg/100ml, respectively. No microbial growth was observed in the formulation. In the accelerated stability tests, no remarkable changes were seen in the product. Total phenolics content was decreased 2.2% during 6 months in 40 ºC. Conclusion: The formulated Prunus domestica syrup could be introduced for further mass production after completing the final required evaluations.